Transmisi Keilmuan Univeritas Al-Azhar Mesir dan Pondok Pesantren di Indonesia - abdul qodir (Jurnal Tamaddun : Jurnal Sejarah dan Kebudayaan Islam, 2021)
Abstract: This research discusses the scientific transmission of Al-Azhar University in Egypt and Islamic boarding schools in Indonesia. Pondok pesantren is the oldest educational institution in Indonesia. The existence of Islamic boarding schools in Indonesia is inseparable from the relationship between Indonesia and the Middle East, especially with Mecca and Al-Azhar Egypt. Indonesian scholars who carry out the Haj pilgrimage are accompanied by studying in Makkah and then continuing their studies at Al-Azhar Egypt. After that, he returned to Indonesia and opened a boarding school in Indonesia. In addition, the curriculum taught in Islamic boarding schools in Indonesia is the books made by Al-Azhar scholars in the fields of jurisprudence, knowledge and interpretation so that there is direct or indirect scientific transmission between Al-Azhar University and Islamic boarding schools in Indonesia. Keywords: Transmission, Science, Al-Azhar University, Egypt, Islamic boarding schools